2019
DOI: 10.1021/acs.jpcc.9b11006
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assembly: Molecular Polymorphs and Their Transitions Triggered Electrically via Water Assistance at the Liquid/Graphite Interface

Abstract: Supramolecular phase transitions triggered by external stimuli constitute a fascinating topic in materials science and supramolecular chemistry. Trimesic acid (TMA) represents a simple molecular building block, and its polymorphs on a solid surface have been extensively explored by scanning probe microscopy and computational simulations. The phase transformations of TMA electrically induced by scanning tunneling microscopy (STM) were previously observed yet noticed to take place rather sporadically. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…26 Recently, we have demonstrated both experimentally and theoretically that water can play a crucial role in assisting the electrically triggered phase transition of TMA. 29 Herein, we chose TPTC as its self-assemblies were randomly constituted by glass-like motifs, which may have low stability and thus have been expected to readily undergo phase transformations upon being subjected to external stimuli. As anticipated, such reversible phase transformations electrically triggered by STM were readily observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Recently, we have demonstrated both experimentally and theoretically that water can play a crucial role in assisting the electrically triggered phase transition of TMA. 29 Herein, we chose TPTC as its self-assemblies were randomly constituted by glass-like motifs, which may have low stability and thus have been expected to readily undergo phase transformations upon being subjected to external stimuli. As anticipated, such reversible phase transformations electrically triggered by STM were readily observed.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] Recently, it has been reported that the direction-oriented electric-field of an STM presents its unique and powerful ability for controlling supramolecular phase transformations as well as chemical reactions at surfaces. [25][26][27][28][29] Although an STM can be operated at the liquidsolid interface, the nucleation and controlled growth of supramolecular assemblies have been less explored. Using a molecular building block of p-terphenyl-3,5,3′,5′-tetracarboxylic acid (TPTC), 30 we report that an external, oriented electric-field of an STM can be utilized to generate STM-bias-related new 2D self-assembled structures, which would be otherwise inaccessible by drop-casting or spin-coating methods.…”
Section: Introductionmentioning
confidence: 99%
“…For carboxylic acids, the deprotonation reaction may be assisted by residual water molecules acting as proton acceptors . The likelihood of this mechanism was corroborated by calculating the Gibbs activation energy barrier for the reaction of proton transfer from TMA to the OH – anion, yielding about 2 kcal/mol in both water and octanoic acid . It is intriguing that the TMA dimeric phase has a close counterpart formed by larger triangular molecules, the BTB oblique phase, which aggregates in the mixed TMA–BTB adsorbate at positive substrate bias voltage …”
Section: Introductionmentioning
confidence: 92%
“…The temperature of the phase transition from the HON arrangement to the dimeric structure can be lowered by substrate modulation. For example, for TMA deposited on a Ag-covered Cu(111) surface, the dimeric phase was observed at 350 K. 14 On less reactive substrates, such as graphite and graphene, the neutral TMA molecules are known to form the HON phase and its higher-order homologues, 17,18 which disintegrate above 350 K. 19 However, switching the substrate bias polarity from negative to positive in the TMA monolayer at the solution−graphite interface at room temperature triggers a reversible phase transition from the HON phase to the closepacked network resembling the dimeric phase, 20,21 which likely originates from the deprotonation of carboxyl groups. For carboxylic acids, the deprotonation reaction may be assisted by residual water molecules acting as proton acceptors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we have reported an electric-field-induced supramolecular crystallization of p -terphenyl-3,5,3′,5′-tetracarboxylic acid (TPTC, Scheme ) at the octanoic acid (OA)/highly oriented pyrolytic graphite (HOPG) interface, where the processes of molecular nucleation and subsequent crystal growth have been successfully revealed by STM . So far, it remains intriguing to explain the mechanism of the “STM-induced” supramolecular phase transition. Therefore, it requires special attention to further explore the stimuli-responsive supramolecular assembling, which may advance materials crystalline engineering . To this end, the comprehensive understanding and effective manipulation of supramolecular crystallizations from both theory and experimental viewpoints are of crucial importance …”
Section: Introductionmentioning
confidence: 99%